Crazy house - Patterson, James, 1947-; Charbonnet, Gabrielle (2017)
In a future world where teenagers are taken, imprisoned, and forced to fight for their survival, well-behaved Cassie will do whatever it takes to save her rebellious twin sister from Death Row
"JIMMY Patterson Books."
Bulletin of the Center for Children's Books
School Library Journal
VOYA (Voice of Youth Advocates Magazine)
Publishers Weekly
14-19
Keywords: Prisoners -- Juvenile fiction; Survival -- Juvenile fiction; Sisters -- Juvenile fiction; Twins -- Juvenile fiction; Conformity -- Juvenile fiction; Science fiction